Ombudsman: uma abordagem brasileiro-dinamarquesa: Ombudsman: a Brazilian-Danish approach - Mello, Shirlei Silmara de Freitas; Bønsing, Sten (Revista de Direito Administrativo e Infraestrutura | RDAI, 2018)
Considering that the Ombudsman concept originated in the Nordic countries, more precisely in Sweden; that Denmark’s high levels of transparency and low levels of corruption favor the development and maintenance of the basis of an efficient administrative proceeding by means of the due process of law in administrative proceedings, and that Brazil, a country of continental dimensions, still has a long way to go before the effective consolidation of the fundamental right to the process, this paper aims at presenting aspects of the Danish Ombudsman’s activity, as well as data regarding ombudsmen offices deployed in Brazil. Such analysis reveals nuances that the control of public administration, procedure wise, by means of deductive reasoning (all state activity should be participatory and transparent; if the administrative proceeding is a state activity, then it should strive for participation and transparency) will be a hard nut to crack. In this sense, it is reasonable to conclude that the definition of the content and the materialization of good administrative practice are crucial factors for the solidification of the due process of law in administrative proceedings in Brazil.